Carbohydrate content and drought resistance in cotton - Souza, José Gomes de; Barros, Antônio Carlos Q. T.; Silva, Jorge Vieira da (Pesquisa Agropecuaria Brasileira, 2014)
Two cultivars of cotton, one more drought resistant (Gossypium hirsutum, r. Marie galante Hutch, cv. Mocó 9193) than the other (G. hirsutum, r. latifolium, Hutch, cv. SU-0450/8909), were grown in a greenhouse to study the effect of drought on the carbohydrate content of leaves, stems and roots and the possibility of using these contents as a screening criterium in breeding. There is a decrease of starch with drought, less important in Mocó than in SU. Starch accumulation in the roots can be a useful parameter in breeding for drought resistance, and a comparison between plants of the original population and after one cycle of recurrent selection for starch content in the roots (in the cultivar SU-0450/8909), shows a heritability of 22.4% and a genetical gain in the cycle of 12,1%.